Happiness and the human development index: Australia is not a paradox - Andrew Leigh; Justin Wolfers (Institute for the Study of Labor (IZA), 2006)
In Happiness and the Human Development Index: The Paradox of Australia, Blanchflower and Oswald (2005) observe an apparent puzzle: they claim that Australia ranks highly in the Human Development Index (HDI), but relatively poorly in happiness. However, when we compare their happiness data with the HDI, Australia appears happier, not sadder, than its HDI score would predict. This conclusion also holds when we turn to a larger cross-national dataset than the one used by Blanchflower and Oswald, when we analyse life satisfaction in place of happiness, and when we measure development using GDP per capita in place of the HDI. Indeed, in the World Values Survey, only one other country (Iceland) has a significantly higher level of both life satisfaction and happiness than Australia. Our findings accord with numerous cross-national surveys conducted since the 1940s, which have consistently found that Australians report high levels of wellbeing.
Keywords: I31; O57; 330; happiness; life satisfaction; Human Development Index; income; Australia; Entwicklungsindikator; Welt; Australien